One year of measurements in Alderney Race: preliminary results from database analysis. (21st August 2020) - Furgerot, L.; Sentchev, A.; Bailly du Bois, P.; Lopez, G.; Morillon, M.; Poizot, E.; Méar, Y.; Bennis, A.-C.
Abstract : The Alderney Race is assumed to have the largest tidal-stream energy potential in the north-western European coastal seas. Interaction of the powerful tidal stream with strong wind, high waves and irregular bathymetry creates hydrodynamic conditions of extreme complexity, with high levels of turbulence. A comprehensive dataset has been created to improve the understanding of physical processes, turbulence, tidal stream and resource variability at the site. The database contains a large amount of oceanographic and meteorological measurements acquired in Alderney Race in 2017–2018. This exceptionally long period of observations (nearly one year) became possible due to modern tools and strategies of data acquisition. The paper presents some significant results from the database analysis. Among many results, we would like to underline the following: (i) a wide range of variability of mean flow and sea state parameters was documented; (ii) exceptionally large values of current velocity (7 m s −1 ) and significant wave height (8 m) were measured during extreme meteorological conditions; (iii) high-frequency variability of current speed during storm events was also found to be very large, with the standard deviation of velocity reaching 0.3 m s −1 in the bottom boundary layer, and 0.6 m s −1 in the surface layer; and (iv) predominant wind and wave direction relative to the flow impacts the wave height and significantly increases the turbulence kinetic energy of the flow. To our knowledge, this is the largest multi-variable database available on potential tidal energy sites. The results of database analysis can represent a significant advance in environmental conditions and resource characterization and provide advanced information to turbine developers. This article is part of the theme issue 'New insights on tidal dynamics and tidal energy harvesting in the Alderney Race'.